Growth Constraints of Formal and Informal Micro and Small -Scale Enterprises and Their Impact on Policy Formulation in Zimbabwe - Mukorera, Sophia (Journal of Economics and Behavioral Studies, 2018)
The new view on MSEs in the informal sector perceives them as being permanent, stable activities comprised of dynamic businesses that affect most economic activities. As such, they need to be considered in economic policies to ensure that they can grow and contribute to the national economy. In Zimbabwe, policies for entrepreneurial development are mainly informed by formal - sector enterprises. This study analysed the similarities and differences in the growth constraints of MSEs operating in the formal and informal sectors in Harare, Zimbabwe . Using descriptive statistics and principal component analysis, the study analysed 21 internal and external growth constraints. The findings were that formal - sector MSEs perceive internal factors as constraining them the most, while informal MSEs perceive external factors as constraining them the most. The study concludes that a common policy approach cannot work in addressing the needs of the two sectors. Sector- specific policies need to be formulated in order for the enterprises in both sectors to fully contribute to the national economy.